2018
DOI: 10.15407/ujpe63.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Thickness Profile of Pulsed Laser-Deposited KY3F10: Ho3+ Thin Films

Abstract: Thin films of KY3F10 : Ho3+ have been successfully prepared by the pulsed laser deposition with a Nd-YAG laser (266 nm, pulse duration of 10 ns, repetition rate of 2 Hz) on a 1 cm × 1 cm silicon substrate in vacuum and for different target-to-substrate distances. The X-ray diffraction (XRD) results show that the films crystallized in the tetragonal polycrystalline phase of KY3F10 (in agreement with JCPDS card No. 27-0465). Theoretical predictions of the thickness profile have been presented, by using some expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The annealing temperature critically affects the luminescent behavior of a material, and the annealing brings about an enhancement or decline in the intensity of TL glow peaks of many TL materials [4][5][6][7][8]. Particularly, in this study of a KY 3 F 10 : Ho 3+ phosphor powder, we observed an enhancement in its TL intensity following the thermal annealing and a shift of the temperature of each TL peak to the higher temperature region.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…The annealing temperature critically affects the luminescent behavior of a material, and the annealing brings about an enhancement or decline in the intensity of TL glow peaks of many TL materials [4][5][6][7][8]. Particularly, in this study of a KY 3 F 10 : Ho 3+ phosphor powder, we observed an enhancement in its TL intensity following the thermal annealing and a shift of the temperature of each TL peak to the higher temperature region.…”
Section: Introductionmentioning
confidence: 58%
“…One of the reasons for shifts in the peak temperatures after the annealing can be due to the cluster formation. The formation of the clusters of traps instead of randomly distributed defects causes a variation in the kinetics of the trapping and recombination processes [1][2][3][4][5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation